Early breast cancer screening using iron/iron oxide-based nanoplatforms with sub-femtomolar limits of detection - Udukala, D. N.; Wang, H. W.; Wendel, S. O.; Malalasekera, A. P.; Samarakoon, Thilani Nishanthika; Yapa, A. S.; Abayaweera, G.; Basel, M. T.; Maynez, P.; Li, Ping; Higgins, Daniel A.; Gadbury, Gary; et al. (My University, 2016)
Proteases, including matrix metalloproteinases (MMPs), tissue serine proteases, and cathepsins (CTS) exhibit numerous functions in tumor biology. Solid tumors are characterized by changes in protease expression levels by tumor and surrounding tissue. Therefore, monitoring protease levels in tissue samples and liquid biopsies is a vital strategy for early cancer detection. Water-dispersable Fe/Fe3O4-core/shell based nanoplatforms for protease detection are capable of detecting protease activity down to sub-femtomolar limits of detection. They feature one dye (tetrakis(carboxyphenyl) porphyrin (TCPP)) that is tethered to the central nanoparticle by means of a protease-cleavable consensus sequence and a second dye (Cy 5.5) that is directly linked. Based on the protease activities of urokinase plasminogen activator (uPA), MMPs 1, 2, 3, 7, 9, and 13, as well as CTS B and L, human breast cancer can be detected at stage I by means of a simple serum test. By monitoring CTS B and L stage 0 detection may be achieved. This initial study, comprised of 46 breast cancer patients and 20 apparently healthy human subjects, demonstrates the feasibility of protease-activity-based liquid biopsies for early cancer diagnosis.
Citation: Udukala, D. N., Wang, H. W., Wendel, S. O., Malalasekera, A. P., Samarakoon, T. N., Yapa, A. S., . . . Bossmann, S. H. (2016). Early breast cancer screening using iron/iron oxide-based nanoplatforms with sub-femtomolar limits of detection. Beilstein Journal of Nanotechnology, 7, 364-373. doi:10.3762/bjnano.7.33
Additional Authors: Ortega, R.;Toledo, Y.;Bossmann, L.;Robinson, C.;Janik, K. E.;Koper, O. B.;Motamedi, M.;Zhu, G. H.
Keywords: Biophotonics; Breast Cancer; Iron/Iron Oxide Nanoparticle; Liquid; Biopsy; Nanodiagnostics Detection